The Controversy in Pedagogical Competence of Early Childhood Education Teachers Towards the Policy of Indonesia National Education Ministry - Surahman, Buyung; Aziza, Mela (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2020)
The study aims to find out and describe what percentage (%) of pedagogical competence controversy of Early Childhood Education teachers in the teaching and learning process to the policy of Indonesia National Education Ministry. This study used a descriptive qualitative method. Data collection techniques were observation, interview and questionnaire. The validity test used the product moment formula while the reliability test used Cronbach's alpha formula. The results of the study showed that mastering characteristics of students is 10,5%; mastering learning theories and learning principles that educating is 10%; curriculum development is 9,1%; learning activities that educating is 20,02%; potential development of students is 7,4%; communication with students is 4,5%; and evaluation and evaluation is 8,0%. It can be concluced that the biggest controversy was found in the mastery of educational learning activities while the smallest mastery of communication.